Calcium signaling regulates ventricular hypertrophy during development independent of contraction or blood flow. (March 2015) - Andersen, Nicholas D.; Ramachandran, Kapil V.; Bao, Michelle M.; Kirby, Margaret L.; Pitt, Geoffrey S.; Hutson, Mary R.
Abstract: In utero interventions aimed at restoring left ventricular hemodynamic forces in fetuses with prenatally diagnosed hypoplastic left heart syndrome failed to stimulate ventricular myocardial growth during gestation, suggesting chamber growth during development may not rely upon fluid forces. We therefore hypothesized that ventricular hypertrophy during development may depend upon fundamental Ca 2 + -dependent growth pathways that function independent of hemodynamic forces. To test this hypothesis, zebrafish embryos were treated with inhibitors or activators of Ca 2 + signaling in the presence or absence of contraction during the period of chamber development. Abolishment of contractile function alone in the setting of preserved Ca 2 + signaling did not impair ventricular hypertrophy. In contrast, inhibition of L-type voltage-gated Ca 2 + influx abolished contraction and led to reduced ventricular hypertrophy, whereas increasing L-type voltage-gated Ca 2 + influx led to enhanced ventricular hypertrophy in either the presence or absence of contraction. Similarly, inhibition of the downstream Ca 2 + -sensitive phosphatase calcineurin, a known regulator of adult cardiac hypertrophy, led to reduced ventricular hypertrophy in the presence or absence of contraction, whereas hypertrophy was rescued in the absence of L-type voltage-gated Ca 2 + influx and contraction by expression of a constitutively active calcineurin. These data suggest that ventricular cardiomyocyte hypertrophy during chamber formation is dependent upon Ca 2 + signaling pathways that are unaffected by heart function or hemodynamic forces. Disruption of Ca 2 + -dependent hypertrophy during heart development may therefore represent one mechanism for impaired chamber formation that is not related to impaired blood flow. Highlights: The mechanisms governing cardiomyocyte hypertrophy during development are unknown. We studied ventricular hypertrophy during chamber formation in a zebrafish model. Cardiomyocyte growth proceeded normally in the absence of contraction and blood flow. Cardiomyocyte growth was dependent upon fundamental Ca 2 + signaling pathways. These findings may inform the understanding of developmental heart malformations.